Dynamic Response of a Four-Pile Group Foundation in Liquefiable Soil Considering Nonlinear Soil-Pile Interaction - Yiliang Yu; Xiaohua Bao; Zhipeng Liu; Xiangsheng Chen (Journal of Marine Science and Engineering, 2022)
Piles, which are always exposed to dynamic loads, are widely used in offshore structures. The dynamic response of the pile-soil-superstructure system in liquefiable soils is complicated, and the interaction between the pile and soil and the pile volume effect are the key influencing factors. In this study, a water-soil fully coupled dynamic finite element-finite difference (FE-FD) method was used to numerically simulate the centrifuge shaking table (CST) test of a four-pile group in saturated sand soil. An interface contact model was proposed to simulate the pile-soil interaction, and a solid element was used to consider the volume effect of the pile. The acceleration responses of the soil and pile, settlement deformation, excess pore water pressure, and bending moment were examined. The results show that the bending moment response of the two piles parallel to the shaking direction show minor differences, while the two piles perpendicular to the shaking direction show almost the same distribution. The values of excess pore water pressure at the same depth but different azimuth angles around the pile are also different. The numerical simulation can accurately reproduce soil deformation and pile internal force during and after dynamic loading.